2012
DOI: 10.4103/0973-029x.92968
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor and microvessel density in oral tumorigenesis

Abstract: Context:Significant increase in vascularity occurs during the transition from normal oral mucosa, through differing degrees of dysplasia, to invasive squamous cell carcinoma (SCC).Aims:To evaluate microvessel density (MVD) and vascular endothelial growth factor (VEGF) expression in oral tumorigenesis and correlate it with the clinicopathological characteristics.Settings and Design:VEGF expression and MVD were quantified immunohistochemically using anti-VEGF and anti-CD34 antibody.Materials and Methods:For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 18 publications
7
47
4
2
Order By: Relevance
“…Although previous reports have demonstrated an association between higher MVD and VEGF expression in OSCC [44,45], in the present study, no correlation was found between MVD and VEGFR1 These results indicate that VEGFR1 and VEGFR2 are related to tissue angiogenesis but may not be the only receptors involved in this process.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Although previous reports have demonstrated an association between higher MVD and VEGF expression in OSCC [44,45], in the present study, no correlation was found between MVD and VEGFR1 These results indicate that VEGFR1 and VEGFR2 are related to tissue angiogenesis but may not be the only receptors involved in this process.…”
Section: Discussioncontrasting
confidence: 83%
“…The tumour microenvironment plays a determinant role in this process, since angiogenic stimuli such as VEGF are not only produced by tumour cells but also by stromal and inflammatory cells [29,45]. In the present study, an increase in epithelial VEGFR1 expression was associated with an increase in epithelial and inflammatory VEGFR2 expression.…”
Section: Discussionmentioning
confidence: 81%
“…The expression of VEGF was significantly correlated with MVD. This is in agreement with the findings of Astekar et al [21]. Our results showed that PRL-3 overexpression was positively associated with the expression of VEGF.…”
Section: Discussionsupporting
confidence: 83%
“…2 In oral tissue, microvessel density is reported to increase as pathology changes from normal to dysplastic to squamous cell carcinoma. 3,4 For breast cancer, some studies have demonstrated a correlation between angiogenesis (microvessel density) and clinicopathologic parameters, although there are discrepancies in results, some of which likely arise as a consequence of the variety of techniques (e.g., immunohistochemistry and visual microscopy) used to assess angiogenesis and microvessel density. 5 Neovascularization plays an important role in cervical intraepithelial neoplasia (CIN) as summarized by Chang et al 6 Microvessel density increases with severity of CIN as assessed by counting of blood vessels in biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%